The Influence of Government Spending, Road Infrastructure and HDI on Indonesia's Economic Growth: Pengaruh Belanja Pemerintah, Infrastruktur Jalan dan HDI terhadap Pertumbuhan Ekonomi Indonesia - Henky Japina; Helmina Simanjuntak; Syamsinah Sirait; Heny Widya; Al Bina (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The study purpose was to analyze the influence of central government spending, road infrastructure development, and the Human Development Index (HDI) on economic growth in Indonesia over the period 1995–2024. Materials and methods. This study employs annual secondary data sourced from the official publications of Statistics Indonesia (BPS) and the Ministry of Finance. The analytical method applied is multiple linear regression to determine the extent of the influence exerted by each independent variable on the dependent variable, namely economic growth. Results. The study found an R-squared (R2) of 0.988291, showing that 98.83% of GDP variation is explained by the model. The F-statistic (0.000) confirms a significant simultaneous effect. Partially, central government spending (X1) has a highly significant positive impact (p=0.000), while road infrastructure (X2) and HDI (X3) do not show significant effects (p > 0.05). Conclusions. The study concludes that central government spending is the primary driver of Indonesia's GDP, whereas road infrastructure and HDI require better optimization to yield immediate economic impacts. These findings suggest a potential